Effect of counseling on breast feeding practices - Rai, Preeti Lata; Sharma, Neetu; Gaur, Ajay; Shingwekar, A G (Indian Journal of Child Health, 2014)
Background: National Family Health Survey-3 data show that the initiation of breastfeeding within 1 h is only 24.5%, whereas the exclusive breastfeeding rates in children <6 month is only 46.4%. Objective: The present study was planned to assess the effect of counseling on breast feeding practices, especially early initiation and sustained exclusive breast feeding (EBF). Method: Cases were pregnant mothers attending antenatal clinic of Kamla Raja Hospital (KRH) (n = 154). Control group comprises of mothers who delivered at government maternity hospital other than KRH (n = 140). The cases were enrolled using structured proforma with written consent. All mothers in case group were counseled antenataly for advantages of early initiation of breastfeeding and helped to initiate breast feeding immediately after birth and again counseled at discharge, on follow-up at the end of 1st month and 3rd month for EBF. The effect was evaluated at end of 1st, 3rd and 6th month in terms of breast feeding practices. Counseling skills used were according to infant and young child feeding practice guidelines. At the end of 3rd month, group and individual counseling was done in case group. In control group, the breast feeding practices were recorded at 1, 3 and 6 month after delivery without any counseling. Results: There was significant increase in early initiation and EBF since birth in case group than in control group with odds ratio of 26. On follow-up at the end of 1st month, 83% (p = 0.001) mothers were practicing EBF in case group, which increased to 86% (p = 0.01) and to 97% (p = 0.006) at the end of 3rd and 6th month, respectively. Effect of counseling in case group for EBF was more in primiparous (78%, 81%, 91%) than in multiparous (48%, 55%, 61%) (p = 0.001, 0.006 and 0.0004 at end of 1st, 3rd and 6th month respectively). On comparing group and individual counseling given at end of 3rd month, the effect evident at 6th month shows, respectively; group counseling was more effective (99%) than individual counseling (95%, p = 0.002). Conclusion: Counseling before delivery and at regular intervals was of utmost importance for early initiation and sustained exclusive breastfeeding. This influenced primiparous mothers more. Group counseling had more impact than individual counseling.